Selective recognition of the di/trimethylammonium motif by an artificial carboxycalixarene receptor. Issue 5 (16th January 2017) - Hanauer, Thomas; Hopkinson, Richard J.; Patel, Kamal; Li, Yu; Correddu, Danilo; Kawamura, Akane; Sarojini, Vijayalekshmi; Leung, Ivanhoe K. H.; Gruber, Tobias
Abstract : We report a simple carboxycalixarene that selectively binds molecules containing di/trimethylammonium moieties in isolation, in cell lysates and when incorporated in histone peptides. Abstract : Chemical tools that recognise post-translational modifications have promising applications in biochemistry and in therapy. We report a simple carboxycalixarene that selectively binds molecules containing di/trimethylammonium moieties in isolation, in cell lysates and when incorporated in histone peptides. Our findings reveal the potential of using carboxycalixarene-based receptors to study epigenetic regulation.